2019
DOI: 10.1088/1367-2630/ab447a
|View full text |Cite
|
Sign up to set email alerts
|

Frequency measurement of the 1 S 0 , F = 5 / 2 ↔ 3 P 1 , F = 7 / 2 transition of 27Al+ via quantum logic spectroscopy with 40Ca+

Abstract: Keywords: trapped ions, mixed ion crystals, quantum logic spectroscopy, frequency standard, metrology P , 7 2 3 1 = = 0.428 133(2).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Comparing this value with the DHF result, we found that the one-electron relativistic effect is 0.073% for the g( 3 P o 1 ) and 0.004% for the g( 1 P o 1 ). Guggemos et al measured the g-factor of hyperfine state 3s3p 3 P o 1 with F = 7/2 in the 27 Al + ion by the quantum logic spectroscopy, and reported two results: 0.42884(1) [25] and 0.428133(2) [26]. Note that the discrepancy between these two values exceeds the experimental error bars of both cases.…”
Section: Calculations and Resultsmentioning
confidence: 99%
“…Comparing this value with the DHF result, we found that the one-electron relativistic effect is 0.073% for the g( 3 P o 1 ) and 0.004% for the g( 1 P o 1 ). Guggemos et al measured the g-factor of hyperfine state 3s3p 3 P o 1 with F = 7/2 in the 27 Al + ion by the quantum logic spectroscopy, and reported two results: 0.42884(1) [25] and 0.428133(2) [26]. Note that the discrepancy between these two values exceeds the experimental error bars of both cases.…”
Section: Calculations and Resultsmentioning
confidence: 99%
“…Atom-laser decoherence (for example, due to laser frequency fluctuations or atomic spontaneous emission) alters this picture by reducing the contrast of the Ramsey fringe by a factor C(T R ) < 1, which depends on the probe duration. In many optical clocks, including the 27 Al + clocks in this letter, decoherence over the relevant timescales is dominated by flicker-frequency noise of the laser [4]. This limits the probe duration that minimizes measurement instability, which has been evaluated analytically and through numerical simulation [5,6,11,12].…”
mentioning
confidence: 99%
“…Both the 1 S 0 and 3 P 0 states in 27 Al + have a magnetic quantum number of F = 5/2. We performed initial correlation spectroscopy experiments on the 1 S 0 , m F = 5/2 ↔ 3 P 0 , m F = 5/2 transition, which has a sensitivity to magnetic fields of −4.2 kHz/G (1 G = 10 −4 T).…”
mentioning
confidence: 99%
See 2 more Smart Citations